Analysis of risk factors for major adverse cardiac events in patients with multiple myeloma - Feng, Yu; Zhou, Jingjing; Chen, Shilv; Li, Shuo; Li, Tianlan; Gao, Yan; Wang, Qianqian; Xu, Yujie; Mao, Chunxia; Liu, Shanshan; Huang, Junxia (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTo identify risk factors for major adverse cardiovascular events (MACE) in patients with multiple myeloma (MM) and to evaluate the performance of an external risk-score–based stratification.MethodsWe retrospectively analyzed 162 newly diagnosed MM patients treated at Qingdao University Affiliated Hospital (2017–2023). Baseline demographics, comorbidities, laboratory and echocardiographic indices, and treatment exposures were collected. MACE (heart failure, acute coronary syndrome, malignant arrhythmias, cardiogenic shock, or cardiac sudden death) were adjudicated during therapy. Multivariable logistic regression identified independent risk factors. Progression-free survival (PFS) was compared by Kaplan–Meier analysis. An externally derived 0–4 point cardiovascular risk score was applied and patients were grouped as low (0–1), intermediate (2), or high (3–4) risk.ResultsMACE occurred in 31/162 patients (19.14%). Independent risk factors included age at diagnosis (OR = 1.059 per year), cigarette smoking (OR = 3.652), anthracycline exposure (OR = 5.850), and ISS stage III (OR = 2.593; 95% CI: 1.108–6.067; all P < 0.05). Using the external risk score, 79, 54, and 29 patients were classified as low, intermediate, and high risk, respectively, with a stepwise rise in MACE incidence from ≈15% (low) to ≈18% (intermediate) and ≈31% (high). Discrimination of the score for MACE was modest (ROC AUC = 0.594). Patients experiencing MACE had significantly shorter PFS.ConclusionAge, smoking, anthracycline use, and ISS stage III independently predict MACE in MM. External risk-score stratification demonstrates a clear gradient of risk but only modest discrimination, underscoring the need for prospective validation and optimization (e.g., integrating disease stage and treatment exposures). These findings support proactive cardio-oncology assessment and tailored therapy—particularly in older, smoking, ISS III, and anthracycline-treated patients.